Implementing drinking water security: the limits of source protection. (21st September 2015) - Cook, Christina
Abstract : While the implementation of drinking water security legislation was an important response to a water quality tragedy in Ontario, Canada, its effect has been circumscribed by hydrosocial relations underlying water governance arrangements. The long‐established land‐use planning—and more recent growth planning and place‐based planning—laws and policies make water management secondary to land whether it is as part of the ecological system, as a resource, or as an amenity. The effect is to subjugate source water protection to land use and, indeed, economic development priorities for resource extraction. The Ontario case shows that implementation of proactive drinking water security through source protection law and policy will be circumscribed by hydrosocial relations that prioritize the economic development. To implement proactive drinking water security will require a fundamental rethinking of the trade‐offs implicit in our existing hydrosocial relations. WIREs Water 2016, 3:5–12. doi: 10.1002/wat2.1117 This article is categorized under: Human Water > Water Governance